Delia Grace Randolph explains why 'The Impact of ILRI' is unique - Grace, Delia (International Livestock Research Institute, 2021)
What makes our pioneering publication 'The Impact of the International Livestock Research Institute' stand apart from others? This question was answered by one of the book's editors, Delia Grace Randolph, Professor of Food Systems at the Natural Resources Institute and joint appointed scientist at ILRI. Read more about ILRI's impact book which covers over 45 years of research for better lives through livestock: ilri.org/ILRI-research-impact